An authority among authorities: knowledge and use of Augustine in the wider Carolingian world. - Timmermann, Josh (Early Medieval Europe, 2020)
What knowledge of Augustine might a Carolingian subject outside the ecclesiastical elite have possessed? If the all‐pervasive influence of Augustine is one of the hallmarks of the Carolingian era, how far into the Carolingian world did that influence (and conscious knowledge of it as 'Augustinian') actually extend? Toward preliminary answers to these questions, this study will consider the presence and various uses of Augustine in textual media that may have reached beyond elite, court‐connected circles, arguing that from such texts Augustine would indeed have been known to ordinary Carolingian Christians, although mainly as one key source of traditional authority operating in fundamental harmony with other such authorities, rather than as a singular figure within the imagination of the Latin Christian west. This ubiquitous emphasis on ostensible agreement among the great authorities of the Christian past should be understood as intimately connected to the Carolingians' efforts at effecting concord and unity in the broader social sphere of the present.